Turning to the larger shoal: are there individual differences in small- and large-quantity discrimination of guppies?. Issue 2 (2nd April 2016) - Miletto Petrazzini, M.E.; Agrillo, C.
Abstract : Quantitative ability in non-human animals represents one of the topics most investigated in cognitive ethology during the last decade. Vertebrates as diverse as mammals, birds and fish proved able to discriminate between two quantities in several ecological contexts. Recently, there has been a wide debate as to whether non-human animals share a single mechanism of numerical representation (commonly referred to as the 'approximate number system', ANS) or instead have also a distinct mechanism for enumerating small numbers (≤ 4), referred to as 'subitizing'. To date, little attention has been devoted to assessing whether individual differences exist in quantity abilities within the boundaries of the two supposed mechanisms. In the present study, we compared the performance of guppies ( Poecilia reticulata ) in small- and large-quantity discrimination. Subjects were inserted in an unfamiliar tank where two groups of conspecifics differing in numerosity were visible, and their spontaneous preference for joining the larger shoal was taken as a measure of their numerical acuity. Each subject was tested in two numerical contrasts: 2 vs 3 and 6 vs 10. A positive correlation in the performance in the two numerical contrasts was found: subjects showing a better performance in the subitizing range also showed a better performance in the ANS range. Our data do not contradict the hypothesis of two distinct mechanisms of numerical representation, but may be more parsimoniously explained by the existence of a single ANS mechanism across the whole numerical range.